Hunger and Satiety Gauge Reward Sensitivity - Cassidy, Ryan Michael; Tong, Qingchun (Frontiers in Endocrinology, 2017)
Many of the neurocircuits and hormones known to underlie the sensations of hunger and satiety also substantially alter the activity of the dopaminergic reward system. Much interest lies in the ways that hunger, satiety, and reward tie together, as the epidemic of obesity seems tied to the recent development and mass availability of highly palatable foods. In this review, we will first discuss the basic neurocircuitry of the midbrain and basal forebrain reward system. We will elaborate how several important mediators of hunger – the agouti-related protein neurons of the arcuate nucleus, the lateral hypothalamic nucleus, and ghrelin – enhance the sensitivity of the dopaminergic reward system. Then, we will elaborate how mediators of satiety – the nucleus tractus solitaries, pro-opiomelanocortin neurons of the arcuate nucleus, and its peripheral hormonal influences such as leptin – reduce the reward system sensitivity. We hope to provide a template by which future research may identify the ways in which highly rewarding foods bypass this balanced system to produce excessive food consumption.